2003
DOI: 10.1140/epje/e2004-00013-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural relaxation of spin-cast glassy polymer thin films as a possible factor in dewetting

Abstract: Reiter [1] has recently reported a situation in which the dewetting of quasi-solid films is linked plastic deformation -rather than viscous flow -resulting from capillary forces. Herein we propose that, in thin films of some glassy polymers -especially poly(methyl methacrylate) (PMMA) -prepared by spin-casting from solvent, structural relaxation might impart sufficient stress to cause plastic deformation. We find that PMMA films decrease in thickness by several percent, which is sufficient to create significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
65
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 37 publications
(46 reference statements)
5
65
0
Order By: Relevance
“…The relaxation of volume (or thickness) in thin films of polymer glasses has been observed by several workers [7][8][9][10][11][12] in neat polymers [7,8] and in polymers containing residual solvent [9][10][11][12][13]. In these previous experiments, measurements of thickness have been made as a function of increasing temperature, and it was observed that the change in thickness (volume) due to relaxation occurs simultaneously with a change resulting from thermal expansivity.…”
Section: ͑1͒mentioning
confidence: 95%
See 2 more Smart Citations
“…The relaxation of volume (or thickness) in thin films of polymer glasses has been observed by several workers [7][8][9][10][11][12] in neat polymers [7,8] and in polymers containing residual solvent [9][10][11][12][13]. In these previous experiments, measurements of thickness have been made as a function of increasing temperature, and it was observed that the change in thickness (volume) due to relaxation occurs simultaneously with a change resulting from thermal expansivity.…”
Section: ͑1͒mentioning
confidence: 95%
“…In these previous experiments, measurements of thickness have been made as a function of increasing temperature, and it was observed that the change in thickness (volume) due to relaxation occurs simultaneously with a change resulting from thermal expansivity. Studies of isothermal relaxation in polymer thin films are much more rare [9,10,12]. The possible effects of molecular confinement and attraction to interfaces on the dynamics of relaxation in polymer thin films are largely unexplored.…”
Section: ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation
“…The final thinning of the film is then due solely to solvent evaporation [2]. Most of the solvent evaporates during the last step of the spin-coating, but it is known that some solvent is still present in the films at the end of the spin-coating [1,3,4] and that the polymer chains are quenched in a nonequilibrated state [5][6][7][8]. Spin-coated films are therefore generally annealed above the glass transition temperature of the polymer to dry the films and let the polymer relax to equilibrium.…”
mentioning
confidence: 99%
“…Spin-coated films are therefore generally annealed above the glass transition temperature of the polymer to dry the films and let the polymer relax to equilibrium. Whereas solvent loss during this drying step (with respect to the initial solvent content) has been extensively studied [3,4,[9][10][11][12][13][14][15], there is hardly any information available on the absolute amount of solvent left in the films.…”
mentioning
confidence: 99%